PERTIMBANGAN HAKIM DALAM MENJATUHKAN EKSEPSI KOMPETENSI RELATIF PADA PUTUSAN PENGADILAN AGAMA MEDAN NO. 252/Pdt/G/2017/PA.Mdn - Simanjuntak, Daniel Ariando Putra; Fahira, Jihan; Zebua, Nico Ondroita; Tarigan, Muhammad Iqbal (JURNAL MUTIARA HUKUM, 2020)
Absolute authority as well as relative belongs to every judicial institution in Indonesia. An example is the Religious Court / Sharia Court in the Nanggroe Aceh Darussalam Province. Absolute authority is almost impossible to be violated by every petitioner whose legal issue wished to be resolved by the court, yet the one that often being violated is the relative competency. As an example of relative competency implementation in religious court is can be seen in the Medan Religious Court decision No. 252 / Pdt / G / 2017 / PA.Mdn. This research uses the method of normative juridical that are analytical descriptive in nature. Through this result, can be known that the Religious Court authority refers to the Article 49 of Law No.3 of 2006 about amendments to law No. 7 of 1989 about the Religious Court and for Nanggroe Aceh Darussalam Province where a religious court is called as a sharia court also tried criminal acts in accordance with Article 3 paragraph (2) of the Aceh Quanun No.6 of 2014 about Jinayat Law. Judges’ consideration in dropping the exception of relative competency is Medan Religious Court Decision No. 252 / Pdt / G / 2017 / PA.Mdn refers to the letter evidence where is convinced by the judges of the defendant’s domicile apart Residential Card, Family Card, Domicile Certificate refers to the statement letter of the defendants and petitioner child who is attending school in Pekanbaru